Leukaemia relapse after allogeneic transplants for acute myeloid leukaemia: predictive role of WT1 expression. (7th January 2013) - Pozzi, Sarah; Geroldi, Simona; Tedone, Elisabetta; Luchetti, Silvia; Grasso, Raffaella; Colombo, Nicoletta; Di Grazia, Carmen; Lamparelli, Teresa; Gualandi, Francesca; Ibatici, Adalberto; Bregante, Stefania; Van, Maria Teresa; et al.
Summary We assessed WT1 expression (expressed as messenger copies/104ABL1) from marrow cells of 122 patients with acute myeloid leukaemia (AML), before and after an unmanipulated allogeneic haemopoietic stem cell transplant (HSCT). The median age was 44 years (15–69), 59% were in first remission, 74% received a myeloablative conditioning regimen and the median follow up was 865 d (34–2833). Relapse was higher in 67 patients with WT1 expression, at any time post‐HSCT, exceeding 100 copies (54%), as compared to 16%, for 55 patients with post‐HSCT WT1 expression <100 copies (P < 0·0001). Similarly, actuarial 5‐year survival (OS) was 40% vs. 63%, respectively (P = 0·03). In multivariate Cox analysis, WT1 expression post‐HSCT was the strongest predictor of relapse (Hazard Ratio [HR] 4·5, P = 0·0001), independent of disease phase (HR 2·3, P = 0·002). Donor lymphocyte infusions (DLI) were given to 17 patients because of increasing WT1 levels: their OS was 44%, vs. 14% for 21 patients with increasing WT1 expression who did not receive DLI (P = 0·004). In conclusion, WT1 expression post‐HSCT is a strong predictor of leukaemia relapse and survival in AML; WT1 may be used as a marker for early interventional therapy.